Job satisfaction of reference staff in the national library board. - Pwee, Kok Ann. (2008)
This study surveys the staff of two adjacent reference departments, the National Reference Library and the Information Packaging team at the National Library Building. The survey used the short form of the Minnesota Satisfaction Questionnaire to measure job satisfaction. Aside from job satisfaction and career identification questions, the questionnaire also collect information about staff education level and career length.